Integrating Network Pharmacology and RT-qPCR Analysis to Investigate the Mechanisms Underlying ZeXie Decoction-Mediated Treatment of Non-alcoholic Fatty Liver Disease - Wu, Jiashuo; Zhang, Fangqing; Ruan, Haonan; Chang, Xiaoyan; Wang, Jingxun; Li, Zhuangzhuang; Jin, Weiyi; Shi, Yue (Frontiers in Pharmacology, 2021)
ZeXie Decoction (ZXD) is a traditional Chinese medicine composed of Alisma orientalis (Sam.) Juzep. and Atractylodes macrocephala Koidz. ZXD has been widely used to treat non-alcoholic fatty liver disease (NAFLD). The mechanistic basis for the pharmacological activity of ZXD, however, remains poorly understood. In this study, we used a network pharmacology approach and investigated the association between ZXD and NAFLD. We identified the active ingredients of ZXD and screened the potential targets of these ingredients, after which a database of relevant NAFLD-related targets were constructed and several enrichment analyses were performed. Furthermore, the ethanol and aqueous extracts of ZXD were prepared and experimental pharmacology validation was conducted using RT-qPCR of the non-alcoholic fatty liver disease (NAFLD) model in Sprague-Dawley (SD) rats. As a result, a herb-compound-target-pathway network model was developed, and HMGCR, SREBP-2, MAPK1, and NF-κBp65 targets were validated. The gene expression results of these four targets were consistent with those of the network pharmacology prediction. Using an integration strategy, we revealed that ZXD could treat NAFLD by targeting HMGCR, SREBP-2, MAPK1, and NF-κBp65.